MECHANICAL AND MORPHOLOGICAL PROPERTIES OF POLY(3-HYDROXYBUTYRATE)-THERMOPLASTIC STARCH/CLAY/EUGENOL BIONANOCOMPOSITES - Rivas, Bernabe L; Garrido-Miranda, Karla A.; Pérez-Rivera, Mónica; Fernández-Blázquez, Juan P.; Monclús, Miguel; Peña-Farfal, Carlos (Journal of the Chilean Chemical Society, 2020)
Food packaging for traditional foods mainly serves to isolate foods from external environmental. For this reason, it is a growing interest in developing active packaging materials that can extend foodstuff shelf-life. Also, it could counteract the level of contamination by plastic in the environment using biodegradable polymers. For this purpose, poly(3-hydroxybutyrate) (PHB)-thermoplastic starch (TPS)/ organically modified montmorillonite (OMMT)/eugenol bionanocomposites were prepared by melt blending. Morphology, thermal, and mechanical properties were determined by comparing the concentration influence of eugenol and clay on the PHB-TPS blend and PHB. X-ray diffraction measurements revealed the existence of exfoliated morphology in the bionanocomposites. Atomic force microscopy imaging (AFM) showed the difference in morphological characteristics of the pure PHB and the prepared bionanocomposites. Roughness analysis from the AFM data indicates that the presence of clay and TPS increases the roughness with respect to PHB. Dynamic mechanical thermal analysis (DMTA) showed that bionanocomposites have an improved storage module. Finally, properties such as hardness and elastic modulus studied by nanoindentation showed a decrease with respect to PHB. The presence of eugenol in the bionanocomposites does not show a significant effect on the different properties.